Enhancement of cooling system for chlorination dipping process in rubber glove manufacturing - Siralan, Arvind (2022)
Since the Industrial Revolution, manufacturing industries had been too focused on outputs and neglecting other factors that might be affecting the cost of production. However, in this era, industrialist have been giving more thoughts and thinking ways to further improve their cost of production in order to maximise their profits. This is where the concept of Lean Manufacturing was used and applied in many industries especially in manufacturing industry. With that, chlorination process is an important process part in the whole powder-free rubber glove manufacturing. The main ingredient of this process is the utilisation chlorine gas to produce chlorine water for the chlorination system process. Based on journal reviews and real-time experience, it was found that chlorination system is very sensitive to temperature, in which led to a great potential of cost saving option if we are able to manipulate the temperature of the chlorine water. With the help of the journal reviews and ideology to save the consumption of chlorine gas via manipulating the temperature, the cost of chlorine gas consumption to produce chlorine water can be reduced. This can be achieved by using the suitable cooling material and cooling liquid. The savings in term of chlorine gas consumption cost and electrical energy savings in the hybrid system design were also calculated in this study. The results for the study are 15% reduction on the overall costs and reduction of energy load by 44% by implementing hybrid cooling system.